RETRACTION NOTICE TO ‘‘N-Terminal pro-Brain Natriuretic Peptide (NT-proBNP) in Stage 1 and Stage 2 Hypertension Patients” [Ina. J. Med. Lab. Sci. Tech. 2019;1(2): 64-67] - Supriati Wila Djami (Universitas Nahdlatul Ulama Surabaya, 2021)
This article has been retracted at the request of the Editor in Chief of the Indonesian Journal of Medical Laboratoy Science and Technology (IJMLST) volume 1 number 2 of 2020 pages 65-67 with DOI: 10.33086/ijmlst.v1i2.1159 because it has been published in the Journal of Health Information volume 17 number 1 year 2019 pages 64-74 with DOI: 10.31965/infokes.Vol17.Iss1.232. Papers submitted to IJMLST should neither published previously nor be under consideration for publication another journal. Therefore, the author should make a statement upon submitting. Reusing data in any form must follow good citation principles, therefore this paper has ethical violations in the scientific publishing system.